European Photography Award 1992 : Deutsche Leasing's Support for the Arts. - Künstlerwerkstatt Bahnhoff Westend, Berlin; Aigner, Carl; von Amelunxen, Hubertus; Chandler, David; Fontcuberta, Joan; Georgieff, Anthony; Kosinska, Barbara; Müller-Pohl, Andreas; Olszowska, Piotr; Valtorta, Roberta; Weiermair, Peter; Zelich, Cristina (Gottingen : European Photography, 1992)
Biswas, Sutapa ; Ceballos, Tomy ; Cirotteau, Régine ; Cortils, Eduardo G.R. ; Dillenkofer, Sinje ; Feyt, Caroline ; Hammerstiel, Robert ; Hervieux, Nathalie ; Olszewski, Janusz ; Pozniak, Marek ; Schlegel, Eva ; Schröter, Erasmus ; Smoczynski, Mikolai ; Vallhonrat, Valentin ; Waelgaard, Line ; Zoppis, Natale
bibliografie
biografie
European Photography Award 1992, , Künstlerwerkstatt Bahnhof Westend, Berlin, December 1992
Engels
boek